2018
DOI: 10.1101/440180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cover crop mixture diversity, biomass productivity, weed suppression, and stability

Abstract: 16 The diversity-productivity, diversity-invasibility, and diversity-stability hypotheses 17 propose that increasing species diversity should lead, respectively, to increased average 18 biomass productivity, increased invasion resistance, and increased stability. We tested 19 these three hypotheses in the context of cover crop mixtures, evaluating the effects of 20 increasing cover crop mixture diversity on aboveground biomass, weed suppression, and 21 biomass stability. Twenty to forty cover crop treatments w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 45 publications
5
30
2
Order By: Relevance
“…Plant diversity has also been shown to influence the stability of these ecosystem functions, with more diverse communities tending to be more temporally stable (less variable) compared with less diverse communities (Tilman et al 2014). Extending these observations to cover crops, speciesdiverse cover crop mixtures should therefore be expected to provide these same functions in agroecosystems and at higher levels than cover crops grown as monocultures (Couëdel et al 2018;Florence et al 2019;MacLaren et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plant diversity has also been shown to influence the stability of these ecosystem functions, with more diverse communities tending to be more temporally stable (less variable) compared with less diverse communities (Tilman et al 2014). Extending these observations to cover crops, speciesdiverse cover crop mixtures should therefore be expected to provide these same functions in agroecosystems and at higher levels than cover crops grown as monocultures (Couëdel et al 2018;Florence et al 2019;MacLaren et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance benefits derived from WCCs, they are often planted in mixtures that include combinations of grasses, mustards, and legumes. This practice is founded on research that has shown positive relationships between WCC functional biodiversity and cropping system benefits (Finney, White, & Kaye, ; Florence, Higley, Drijber, Francis, & Jindquist, ). For example, combinations of specific grass and legume cover crops were determined to increase levels of nitrogen‐sequestration and nitrogen contributions to the subsequent cash crop compared to monocultures of the constituent grasses or legumes (Kaye et al., ; Ranells & Wagger, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of cover crops performed better under dry and warm conditions than the before‐mentioned single cover crop species . Cover crop mixtures better compensate temporal and spatial variation in growing conditions, and thus tend to outperform single species in the long term by ensuring that at least some species grow every year at every site .…”
Section: Cover Crops In Temperate Areas As Part Of Iwmmentioning
confidence: 91%
“…Cover crop mixtures better compensate temporal and spatial variation in growing conditions, and thus tend to outperform single species in the long term by ensuring that at least some species grow every year at every site . This hypothesis was proven in a 4‐year field study at 11 locations testing 18 cover crop species in mixtures and as a pure stand . Cover crop mixtures, on average, produced more aboveground biomass and suppressed more weeds than the average of single cover crops.…”
Section: Cover Crops In Temperate Areas As Part Of Iwmmentioning
confidence: 95%
See 1 more Smart Citation